Digital Workload and Technostress on Employee Performance: The Mediating Role of Digital Fatigue: Beban Kerja Digital dan Teknostres terhadap Kinerja Karyawan: Peran Mediasi Kelelahan Digital - Astri Sabrina Anggraini; Fitri Wulandari (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2026)
This study investigates how digital workload and technostress affect employee performance, with digital fatigue as a mediating factor in digitally intensive work environments. Using a quantitative survey approach, data were collected from 201 respondents selected through purposive and snowball sampling and analyzed using partial least squares structural equation modeling (PLS-SEM). Results reveal that digital workload has a significant direct positive effect on performance but does not indirectly affect it through digital fatigue. In contrast, technostress has no direct effect on performance, but significantly impacts performance indirectly through digital fatigue. These findings highlight the complex dynamics between digital stressors and worker outcomes, suggesting that organizations should differentiate between types of digital pressures when designing interventions. Practical implications include the need for targeted strategies to manage technostress and digital fatigue, such as digital detox programs, mindful technology use policies, and workload design tailored to digital work contexts.